Political Philosophies and Positive Political Psychology: Inter-Disciplinary Framework for the Common Good - Kobayashi, Masaya (Frontiers in Psychology, 2021)
This paper explores the relationship between positive psychology and political philosophy, revealing an inter-disciplinary approach that speaks to the concerns of the common good. Since positive psychology has been expanding its reach into social and political spheres, its relationship to philosophical arguments has been worthy of exploration. Positive psychology is associated with utilitarianism, and aspects of hedonic psychology. However, an alternative concept of eudaimonic well-being has enabled this psychology to have links to other political philosophies. Therefore, this paper provides an overview of contemporary political philosophies: first, it discusses the debate between liberalism and communitarianism, and secondly, it summarizes the subsequent developments of liberal perfectionism, capability approach, and deliberative democracy. Then, the configuration of these political philosophies is indicated by the figure of two axes of 'individual/collective' and 'ethical/non-ethical.' The following section compiles the inter-relationships between the conceptions of citizenship, justice, and well-being, regarding the main political philosophies: egoism, utilitarianism, libertarianism, liberalism, communitarianism, and conservatism. Utilitarianism is associated with happiness, while liberalism and libertarianism rely on the concept of rights, which is almost equal to the idea of justice. Accordingly, utilitarianism is a philosophy of well-being, while liberalism and libertarianism are philosophies of justice. However, there is little connection between well-being and justice in these philosophies because the two kinds of philosophies are incompatible. The latter kind criticizes the former because the maximization of happiness can infringe on people's rights. Moreover, these philosophies do not particularly value citizenship. In contrast, communitarianism is intrinsically the political philosophy of citizenship most attuned to increasing well-being, and it can connect an idea of justice with well-being. The final part offers a framework to develop an inter-disciplinary collaboration. Positive psychology can provide the empirical basis of the two axes above concerning political philosophies. On the other hand, the correspondence makes the character of political philosophies clearer. While libertarianism and liberalism correspond to psychology as usual, utilitarianism and communitarianism correspond to positive psychology, and the latter can be regarded as positive political philosophies. This recognition leads to the interdisciplinary framework, enabling multi-disciplinary collaboration, including work with the social sciences, which could benefit the common good.